Community engagement in water, sanitation and hygiene in sub-Saharan Africa: does it WASH?. (17th January 2022) - Tsekleves, Emmanuel; Fonseca Braga, Mariana; Abonge, Christiana; Santana, Marli; Pickup, Roger; Yongabi Anchang, Kenneth; de Pippo, Tommaso; Semple, Kirk; Roy, Manoj
Abstract: This transdisciplinary literature review paper aims at addressing the literature lacuna in community engagement and water, sanitation and hygiene (WASH) in sub-Saharan countries. By responding to a set of identified WASH-related questions to community engagement, it explores through different disciplinary lenses the challenges and opportunities in this significant area that impacts human health. This transdisciplinary review brought together the disciplines of water engineering, environmental microbiology, public health and infectious disease, design research, women and gender studies, and developmental studies. It examined over 430 papers with 29 papers included in the final review. The main findings suggest integrating women into leadership roles in community water management and water and sanitation programmes can lead to more sustainability and can make water projects more effective. Second, cultural preferences should be a key factor when planning and implementing WASH technologies and interventions. Third, for community engagement to be effective, it should be done with intentionality and over a longer period; and employ existing culturally embedded leadership structures, such as schoolteachers, religious leaders and train change agents. HIGHLIGHTS: Successful community engagement in WASH requires intentionality and activation over a longer period of time. There are benefits in working with community leaders to establish peer education programmes on WASH. Engaging communities through co-design and co-production provides a powerful tool for wider community acceptance and ownership of WASH interventions. It is critical to involve women in community WASH.